HAS INCLUSIVE HEALTH ACCESS IN JAKARTA'S PUBLIC HEALTH CENTER BEEN FULFILLED? - Jane Kartika Propiona (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2023)
Background: Each individual, including persons with disabilities, has a guaranteed right to access healthcare services. Indonesia has ratified the United Nations Convention on the Rights of Persons with Disabilities (CRPD) through Law No. 19 of 2011. However, PWDs still experience difficulties and restrictions in accessing health services. Aims: Examine the fulfillment of inclusive health access for PWD in public health services as a form of inclusivity in health development in Jakarta. This research will finally analyze whether local regulations have accommodated the fulfillment of health rights for PWDs. Method: Using qualitative and descriptive methods by raising case studies that are used in-depth and thoroughly. This study was conducted in three public health centers in South Jakarta. The reason for choosing the location is because Jakarta is an area that has regional regulations on PWD, and the proportion of PWD is 22.1% nationally. The informants in this study were selected by purposive sampling techniques involving 15 informants who conducted in-depth interviews. Results: The mandate of local regulations has not realized inclusive health services for PWD. Marked by lack of information, the absence of health services specifically even though there has been social assistance in the form of KPDJ (Jakarta Disability Card), accessibility that is not yet disability-friendly, and commitment from local governments that are lacking because there is no evaluation, especially in the health sector so that the environment is not inclusive. Conclusion: Providing access to health services for PWD in South Jakarta public health centers is still not inclusive. Policy evaluation is needed, considering that local regulations on PWD have been revised in 2022. Data collection on the number of PWDs in the Puskesmas work area needs to be carried out to meet their health needs. Keywords: access, disability, health, inclusive, public health center